Using the Jigsaw Teaching Method to Enhance Internal Medicine Residents' Knowledge and Attitudes in Managing Geriatric Women's Health - Patricia Ng; Kimberly Kranz; Ruth Abeles; Danielle Schwartz; Susan Lane (Association of American Medical Colleges, 2020)
Introduction Although studies surveying internal medicine (IM) residency program directors identify geriatric women's health as an essential curriculum topic, there are limited published women's health curricula for IM residents. Our IM residency program performed a needs assessment, which revealed that the majority of residents were unsatisfied with our current curricula and most were not confident managing geriatric women's health. We developed and assessed a structured curriculum to improve IM residents' knowledge and confidence in addressing geriatric women's health. Methods This 2-hour interactive workshop used the jigsaw teaching method (a cooperative learning strategy where peers deliver specific content in teams) to teach 84 categorical IM residents of all PGY levels about the diagnosis and management of menopause, osteoporosis, urinary incontinence, and abnormal uterine bleeding. Participants completed a pretest and immediate posttest to assess knowledge and confidence about the targeted topics. We compared baseline and postworkshop responses using chi-square and Wilcoxon signed rank tests. Results Seventy-four (88%) IM residents completed the pretest, and 62 (74%) completed the posttest. Mean knowledge scores improved from 51% to 69% (p < .0001). Residents who reported feeling somewhat confident or confident in addressing women's health topics increased from 14% to 44% (p < .0001). The majority were satisfied or very satisfied with the workshop (94%) and requested additional women's health education (92%). Discussion Our results suggest that workshops using the jigsaw teaching method can effectively increase IM resident knowledge and confidence in managing geriatric women's health.